Navigating the Digital Shift: Exploring the Impact of Technology on Management Practices in Small and Medium Enterprises (SMEs) in Nepal - Adhikari, Shankar Nath; Molla, Nsiruddin (Nepalese Journal of Management and Technology, 2024)
This study investigates the impact of digital technology on management practices in small and medium enterprises (SMEs) in Nepal. The main objective is to understand how digitalization influences decision-making, customer support, and collaboration and communication within these organizations. Utilizing a mixed-methods approach, data were collected from 300 management members and employees across seven SMEs in various sectors. The study combined quantitative surveys and qualitative interviews to provide a comprehensive view of the digital shift. The findings reveal that digitalization significantly enhances decision-making, customer support, collaboration, and communication. Improved access to data and advanced analytical tools enables managers to make more informed and timely decisions, fostering agility and responsiveness in business operations. Digital tools such as customer relationship management (CRM) systems and support software have greatly improved customer support by enabling faster response times, personalized service, and better issue tracking. Furthermore, communication platforms and collaboration tools like project management software and team messaging apps enhance collaboration and communication among employees, facilitating better information sharing, coordination, and teamwork. These tools streamline workflows, reduce manual errors, and increase overall productivity. These insights underscore the essential role of digitalization in modernizing management practices in Nepalese SMEs, helping them remain competitive in a digital global market. The study also addresses the challenges of digital transformation, including the need for ongoing training and adaptation to new technologies. It concludes with recommendations for SMEs to effectively leverage digital technologies to optimize management functions, enhance customer support, and improve collaboration and communication, ensuring sustainable growth in the digital era.